Development of Learning Method Blended Flipped Classroom of in Algorithm and Programming - Mariam, Metta; Wibawanto, Hari; Supraptono, Eko (Universitas Negeri Semarang, 2018)
The purpose of this research is to develop Â learning e-learning-based as a solution in improving attitudes, interests and competence of student learning in particular PTIK employee class in the subject matter of programming dam algorithm looping /looping.The research method used follows the steps of Sugiyono but the researcher only took 4 (four) stages of research, namely 1) preliminary stage, 2) development stage, 3) validation stage and 4) implementation phase. The essence of this study is to look for differences between attitudes, interests and learning competencies before and after the application of-based elearninglearning. The results showed a difference in attitude percentage of 12.13%, the difference in percentage interest of 18.23% and the results of student learning competencies were seen from the average score of pretest of 73.16 and theaverage score Â posttests of 89.63 with the test results the gain is 1 with high criteria. Thus it can be concluded that the results of the development oflearning in blended themethod flipped classroom can improve the attitudes, interests and learning competencies of employees of the PTIK class. This finding is the development of the blended learning Â method of flipped classroom, a learning method that can be applied at the college level that has employee classes.learning in Blended themethod flipped classroom can be used as a reference in new learning in college.